Identification and freedom to operate analysis of potential genes for drought tolerance in maize (2017)
Drought tolerance is an important character for agricultural crops, particularly corn. Genes confering this feature can be patented, thus hindering their use. From a thorough analysis, three genes (DREB, ZAT10 and CspB) were identified and their sequences were captured in the NCBI database. From these sequences and using free software tools, expression cassettes -including regulatory regions (promoters E35S + Pleader, Ubi-1, rab17; terminators Trub, Tnos)- were designed. Patent searches were conducted in international databases (The Lens and PATENTSCOPE). Four patents and an application were found. In the Colombian national database of the Superintendence of Industry and Commerce (SIC), only the application made through PCT was identified. The claims and nucleotide sequences contained in the application were analyzed and it was found that they do not affect the expression cassettes designed. There is freedom to operate for these constructs and it is possible to continue developing drought-tolerant GM maize lines for the domestic market.